Development of an Educational Spinner Board Game to Improve Students’ Understanding in Social Studies at Darul Falah Islamic Elementary School - Hawari, Fadhil Aziz; Rahmania, Nurani (PGMI, STAI Miftahul Ula Nganjuk, 2024)
The development of the Spinner Board Educational Game for Grade V students at Darul Falah Islamic Elementary School, Pandan Arum, Baron, Nganjuk, was motivated by existing phenomena in the school, namely the suboptimal use of learning media. This condition occurred because the learning process tended to focus more on classroom control, while instruction still relied on assignment-based methods. As a result, teachers often utilized the surrounding environment as learning media. The objectives of this study are: (1) to describe the development of Spinner Board learning media for Theme 7, “Cultural Diversity in My Country,” for Grade V students at Darul Falah Islamic Elementary School, Pandan Arum, Baron, Nganjuk; and (2) to describe the results of the trial implementation of the Spinner Board Educational Game for Grade V students at Darul Falah Islamic Elementary School, Pandan Arum, Baron, Nganjuk in the 2023/2024 academic year. The research method employed in this study is the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) with a Research and Development (R&D) research design. The researcher focused on developing Spinner Board game media to meet students’ learning needs. Data analysis techniques included interviews and questionnaires, and the data types consisted of qualitative and quantitative data. The research subjects consisted of 12 students participating in the Spinner Board game. Data collection techniques involved classroom observations and questionnaires administered to teachers and students, as well as validation sheets completed by media experts and material experts. Overall, the research results indicate that the media expert validation achieved a percentage score of 90%, while the material expert validation reached 96%. Student responses to the media obtained a score of 92% during the first trial stage, with a “very good” qualification, indicating that students were able to understand the material and use the media effectively. Meanwhile, the teacher’s response to the media reached 89%. Therefore, the Spinner Board learning media is considered highly feasible for use as an instructional medium.